Antibiotic resistance and virulence characteristics of Vibrio vulnificus isolated from Ningbo, China - Xu, Xiaomin; Liang, Shanyan; Li, Xin; Hu, Wenjin; Li, Xi; Lei, Liusheng; Lin, Huai (Frontiers in Microbiology, 2024)
Vibrio vulnificus (V. vulnificus) is a deadly opportunistic human pathogen with high mortality worldwide. Notably, climate warming is likely to expand its geographical range and increase the infection risk for individuals in coastal regions.However, due to the absence of comprehensive surveillance systems, the emergence and characteristics of clinical V. vulnificus isolates remain poorly understood in China.In this study, we investigate the antibiotic resistance, virulence including serum resistance and hemolytic ability, as well as molecular characteristics of 21 V. vulnificus isolates collected from patients from Ningbo, China. The results indicate that all isolates have been identified as potential virulent vcg C type, with the majority (16/21) classified as 16S rRNA B type. Furthermore, these isolates exhibit a high level of antibiotic resistance, with 66.7% resistance to more than three antibiotics and 61.9% possessing a multiple antibiotic resistance (MAR) index exceeding 0.2. In term of virulence, most isolates were categorized as grade 1 in serum resistance, with one strain, S12, demonstrates intermediate sensitive in serum resistance, fall into grade 3. Whole genome analysis disclosed the profiles of antibiotic resistance genes (ARGs) and virulence factors (VFs) in these strains. The strains share substantial VF genes associated to adherence, iron uptake, antiphagocytosis, toxin, motility, etc. In particular, key VFs such as capsule (CPS), lipopolysaccharide (LPS) and multifunctional autoprocessing repeat-in-toxin (MARTX) are prevalent in all isolates. Specifically, S12 possesses a notably high number of VF genes (672), which potentially explains its higher virulence. Additionally, these strains shared 6 ARGs including PBP3, adeF, varG, parE and CRP, which likely determine their antibiotic resistance phenotype. In conclusion, our study provides valuable baseline information for clinical tracking, prevention, control and treatment of V. vulnificus infections.